Citizen participation in transport planning: its history and achievements - Heo Eok, author; Kim, Eun-Hee, author; Kim, Joung-youl, author; Kim, Kwang Sik, author; Lim, Jae-kyung, author; Lim, San-jin, author; Myeong, Myo-hee, author; Oh, Ji Seop, author (Korea : The Korea Transport Institute (KOTI), 2015)
Includes bibliographical references.